The innovation secrets of Steve Jobs : insanely different : principles for breakthrough success. - Gallo, Carmine, ....- (New York : McGraw-Hill, 2011)
Introduction: What the World Needs Now Is More Jobs Steve JobsChapter 1 What Would Steve Do? 1 Principle 1 Do What You Love Chapter 2 Follow Your Heart Chapter 3 Think Differently About Your Career Principle 2 Put a Dent in the Universe Chapter 4 Inspire Evangelists Chapter 5 Think Differently About Your Vision Principle 3 Kick-Start Your Brain Chapter 6 Seek Out New ExperiencesChapter 7 Think Differently About How You Think Principle 4 Sell Dreams, Not Products Chapter 8 See Genius in Their Craziness Chapter 9 Think Differently About Your Customers Principle 5 Say No to 1,000 Things Chapter 10 Simplicity Is the Ultimate Sophistication Chapter 11 Think Differently About Design Principle 6 Create Insanely Great Experiences Chapter 12 We're Here to Help You Grow Chapter 13 Think Differently About Your Brand Experience Principle 7 Master the Message Chapter 14 The World's Greatest Corporate Storyteller Chapter 15 Think Differently About Your Story One More Thing...Don't Let the Bozos Get You Down